Development of a multi-epitope vaccine against Acinetobacter baumannii: A comprehensive approach to combating antimicrobial resistance - Masoumeh Beig; Mohammad Sholeh; Safoura Moradkasani; Behzad Shahbazi; Farzad Badmasti (PLoS ONE, 2025)
Background The World Health Organization has categorized Acinetobacter baumannii (A. baumannii) as a critical priority pathogen due to its high antibiotic resistance. This resistance complicates treatment and underscores the urgent need for new antibiotics and strategies. This study developed a multi-epitope vaccine (MEV) to address this significant public health threat. Methods This study employed a computational approach to design MEV targeting A. baumannii strain VB7036. Surface-exposed proteins were identified using PSORTb and TMHMM, followed by antigenicity and allergenicity predictions using VaxiJen and AlgPred. Linear B-cell epitopes and MHC-II binding sites were predicted using BepiPred and TepiTool, while physicochemical properties were analyzed with ExPASy ProtParam and Protein-Sol. The MEV construct was validated through molecular docking with TLR2 and TLR4 using HDOCK, revealing strong binding interactions. Molecular dynamic simulations confirmed the stability of the vaccine-receptor complexes, while PCA analysis indicated minimal conformational transitions. Immune simulations were conducted using C-ImmSim online software. Results This study identified eight OMPs from A. baumannii strain VB7036 as potential immunogenic targets. MEV was designed using five critical B-cell epitopes from four proteins based on their antigenicity, non-allergenicity, and physicochemical properties. This MEV demonstrated strong binding to TLR2 and TLR4, indicating effective immune activation. Molecular dynamics simulations confirmed the structural stability of the MEV-TLR complexes. In silico immune simulations revealed that the MEV induced robust humoral and cell-mediated immune responses, including increased antibody production, T-cell activation, and cytokine release, suggesting the MEV’s potential as an effective vaccine candidate for A. baumannii. Conclusion This study developed an optimized MEV and identified novel drug targets against A. baumannii, providing broad protection against multidrug-resistant A. baumannii strains. MEV demonstrated significant potential due to its favorable physicochemical properties, as confirmed by molecular docking and dynamic simulations. However, more in vitro and in vivo studies are required to verify the drug’s effectiveness.